Furious Hours : Murder, Fraud, and the Last Trial of Harper Lee - Cep, Casey N. (New York : Alfred A. Knopf, 2019)
"The stunning true story of an Alabama serial killer, and the trial that obsessed the author of To Kill a Mockingbird in the years after the publication of her classic novel--a complicated and difficult time in her life that, until now, has been very little examined. Willie Maxwell was a Baptist reverend in Alabama; he also happened to be a serial killer. Between 1970 and 1977, his two wives and brother all died under suspicious circumstances -- each with hefty life insurance policies taken out by none other than the Reverend himself. With the help of a savvy lawyer, Maxwell escaped justice for years. Then, the teenage daughter of his third wife perished. At the funeral, the victim's uncle shot the Reverend dead in a church full of witnesses--and was subsequently acquitted of the murder, thanks to the same savvy lawyer who had represented the Reverend for all those years. Sitting in the audience during the trial was Harper Lee, who had traveled from New York to her native Alabama with an idea of writing a book about the case. Now, Casey Cep brings this nearly inconceivable, gripping story to life on the page: from the shocking murders to the chicanery of insurance fraud to the courtroom drama. At the same time, it is a vividly told, elegiac account of Harper Lee's quest to write a second book after To Kill a Mockingbird, and a deeply moving portrait of this beloved writer's struggle with fame, success, and the mysteries of artistic creativity"--
Includes bibliographical references (pages 307-314).
Keywords: Maxwell, Willie; Lee, Harper; Serial murders -- Alabama; Murder -- Investigation -- Alabama; Trials (Murder) -- Alabama; BIOGRAPHY & AUTOBIOGRAPHY / Literary; TRUE CRIME / Murder / Serial Killers; HISTORY / United States / State & Local / South (AL, AR, FL, GA, KY, LA, MS, NC, SC, TN, VA, WV); True crime stories